If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8p + 13 = 5 + -13 Reorder the terms: 13 + 8p = 5 + -13 Combine like terms: 5 + -13 = -8 13 + 8p = -8 Solving 13 + 8p = -8 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + 8p = -8 + -13 Combine like terms: 13 + -13 = 0 0 + 8p = -8 + -13 8p = -8 + -13 Combine like terms: -8 + -13 = -21 8p = -21 Divide each side by '8'. p = -2.625 Simplifying p = -2.625
| (2g)(7g)= | | 9q-13+3(q+8)=7 | | -28+15n-22z=31 | | 9q-13+3(a+8)=7 | | m-4/9=-2,67/90 | | 3x+2738=6714 | | 9x-7y=31 | | 3x+2238=6714 | | 28x-4=49x^2 | | 4(-7x+5)-2x=5 | | 4x-10=-4+22 | | 28x-4=-49x^2 | | log(9x-8)=0 | | 8x-2y=-2 | | 90=5x-2x-30 | | Ax^3-ay^3-bx^3+by^3=0 | | 5(m-1)=10 | | 11x+2y=-12 | | xq+1n=300 | | 7x+2+5x=-10 | | 2m-6=4+2m | | 12x-15+2x+4=24 | | 26=(5-4)f | | 3x^2+24+18x=0 | | 4x+6y=-2 | | 18(7-2x)=7+2x | | 3x+4(-x-8)=-42 | | -9x-(-27)= | | 1.6k=480 | | 12r+5+3r=-5 | | -101-4x+11x=60 | | 2a-11=-8a+10 |